Factors and determinants associated with prevalence of stunting and thinness among adolescents of Tharparkar, Sindh, Pakistan: A community-based study - Aisha Memon; Zulfiqar Ali Laghari; Ayaz Ali Samo (PLoS ONE, 2025)
Stunting and thinness are significant public health concerns for developing countries, including Pakistan. Previously conducted studies in Tharparkar have focused on stunting, and thinness, in children, and micronutrient deficiency, However, there was a paucity of literature on prevalence rates and risk factors associated with stunting and thinness among adolescents in Tharparkar, Sindh, Pakistan. This study aimed to assess the demographic and dietary factors related to the prevalence of stunting and thinness among adolescents in Tharparkar. A community-based cross-sectional study was conducted from June 2022 to August 2022. Most populated Union councils of all sub-districts of Tharparkar district were selected for sampling. A multi-stage clustering sampling strategy was used. Healthy adolescents with ages≥10 to ≤19 years were included in the study. Anthropometry was performed using standard methods. Stunting and thinness were defined as per WHO criteria. Dietary assessments were conducted on a weekly recall basis. Mean Frequency and chi-square were computed using SPSS software. The overall mean age of the study participants was 14.11±2.43 years, and the mean weight was 36.842±8.83 kgs. The mean height of the study participants was 149.0151±11.27 centimeters. The mean height for age z score was -1.3094±1.17. The mean body mass index for age z score was -1.5473±1.27. Among 599 participants the overall prevalence of stunting and thinness was 26.7% and 35% respectively. Risk factors such as late adolescence (χ2=10.55 p=0.005), illiteracy, and less education (χ2=8.41 p=0.03), the rural area (χ2=3.92 p=0.04) significantly associated with an increased prevalence of stunting. The risk factors such as male (χ2=13.11 p<0.0001), infrequent consumption of eggs (χ2=5.2 p=0.02), and infrequent consumption of fresh vegetables (χ2=5.2 p=0.02) were associated with an increased prevalence of thinness. This study underscores the urgent need for comprehensive nutritional programs that could focus on vulnerable demographic groups. Interventions should focus on improving dietary intake.